Attractor States in Second Language Development - Ashley Beccia (Studies in Applied Linguistics & TESOL)
Identifying changing patterns of stability and variability is crucial when examining second language development (SLD) from a complex dynamic systems theory (CDST) perspective (Larsen-Freeman, 2020). By studying attractor states, or recurrent patterns of stability, light can be shed on the underlying dynamics of a complex dynamic system (van Geert & Verspoor, 2015). In the context of SLD, attractor states can be observed in individuals’ linguistic behaviors, as well as learners’ interactions with others (Hiver, 2014; van Geert & Verspoor, 2015). As such, attractor states have been cited in recent SLD literature (e.g., Amerstorfer, 2020; Evans & Larsen-Freeman, 2020; Syed et al., 2021; Gillies & Roger, 2022). The conceptual unpacking of attractor states can therefore be invaluable for SLD scholars seeking to enter the realm of CDST. Accordingly, serving as a stepping stone for those looking to foray into the CDST paradigm, this forum piece offers a definition of attractor state, identifies and describes different types of attractor states, clarifies some possible misconceptions about attractor states, and provides a few examples of attractor states in SLD.